Identification of Acanthocephala on Water Monitor Lizard (Varanus salvator) Human Consumed in Sidoarjo - Ahmad Herdianto Wicaksono; Emmanuel Djoko Poetranto; Tatik Hernawati; Boedi Setiawan (Universitas Airlangga, 2020)
Water monitor lizards are consumed by humans for its meat. The demand this reptile consumption because the taste and belief of the people in healing disease. Based on habitat and food, they have the potential to transmit zoonosis and have a high possibility of being infested by parasites. One of the possible disease that could infect water monitor and transmitted to human is acanthocephaliasis, infection from Acanthocephalan. Which previous research found Acanthocephala on intestine of frog. This research aims to know and identify Acanthochepala worms that infect water monitor lizards. Based on the results, 40 samples were used and there are 2 positive samples with Acanthocephalan in the body cavity.